Biting Behaviour of The Filarial Vector Mosquito, Culex quinquefasciatusSay,in an Urban Area - Rani G Elizabeth; A Surendran; A.J Thatheyus (Journal of Plant and Animal Ecology, 2020)
Mosquitoes depend on blood meal for the development of their eggs into offsprings. By knowing the biting behaviour of mosquitoes, we may control mosquito-borne diseases and manage the mosquitoe menace successfully. The present study has been designed to study the biting behaviour of the filarial vector, Culex quinquefasciatus Say, in Madurai, Tamil Nadu, India from July to November 2006. This period was selected as mosquitoes are prevalent during this rainy season. Biting was more during September, October and November and the maximum of 28 caught/man/hour was recorded in November. It is predominantly an exophilic biter, but biting was also noticed as maximum inside the house during July in the study. The density of the biting population in the first floor was more than that of the second floor, which indicated the existence of vertical stratification in the biting behaviour of Cx quinquefasciatus.
Keywords: Mosquitoes